Labor Administration and Regional Integration - Casale, Giuseppe; Cabegin, Emily Christi A. (Philippine Journal of Labor and Industrial Relations; Vol 33 (2015): Philippine Journal of Labor and Industrial Relations, 2020)
Globalization and deepening regional integration, such as the establishment of the ASEAN Community, has engendered challenges that member states commonly share, and requires inter-country coordination and cooperation for more effective governance of labor issues, especially those beyond the confines of national labor administrations. This paper describes the best practices of regional collaboration in the ASEAN region for more effective governance of cross-border migration, presents an overview of remaining challenges, and provides a set of suggestions for further strengthening national and regional labor administrations towards the attainment of more productive and decent employment of workers including migrant workers.